IMPLEMENTATION PODCAST AND LEARNING VIDEO TO CONNECTING IN DISTANCE LEARNING ON HIGHER EDUCATION - Nadhianty, Ardhina; Purnomo, Agus (Proceeding of International Conference on Islamic Education (ICIED); Vol 5 No 1 (2020): Proceeding of International Conference on Islamic Education (ICIED), 2021)
Education always changes according to changes that occur in society. The world is hit by the Covid-19 pandemic, which has changed the social order in all fields, including education. This situation has led to the change in the education model in Indonesia to become Distance Learning, which provides new challenges for all those involved in teaching and learning activities to apply the right models and media in the learning process. The purpose of this study is to explain the implementation of the use of podcasts and instructional videos in distance learning conducted in universities. The method used in this research is descriptive. The data in this study came from primary data and secondary data. The data collected was processed through the editing, coding, tabulating, and conclusion stages. This study explains that the application of podcasts and instructional videos in distance learning in tertiary institutions provides various opinions. Podcasts and learning videos are flexible, practical, creative, easily accessible anywhere and anytime, and can explain subject matter quite well in distance learning. However, the two media both need an internet network to access it. Moreover, that condition becomes an obstacle for students whose places there are not a smooth internet network available.